2019
DOI: 10.32353/khrife.2.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Methods of Financial and Economic Examinations to Determine Insolvency

Abstract: The article describes the methods of financial and economic examinations to determine the insolvency of a company in the Baltic countries, Republic of Armenia, Ukraine, Republic of Belarus, the Russian Federation and Republic of Kazakhstan. The signs of insolvency regulated in legislation of the countries, and international requirements for the validation of expert methods are presented in the article. The authors present the results of a comparative analysis of the considered methods for assessing insolvency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Courts do not apply the developed and verified bankruptcy forecasting models in practice (Spieciute et al 2013). The financial and non-financial indicators for detecting bankruptcy fraud are specified in legal acts of the Russian Federation, the Republic of Belarus, Ukraine (Liodorova et al 2019), but there is no information about the application of any bankruptcy forecasting model to establish evidence of bankruptcy fraud in these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Courts do not apply the developed and verified bankruptcy forecasting models in practice (Spieciute et al 2013). The financial and non-financial indicators for detecting bankruptcy fraud are specified in legal acts of the Russian Federation, the Republic of Belarus, Ukraine (Liodorova et al 2019), but there is no information about the application of any bankruptcy forecasting model to establish evidence of bankruptcy fraud in these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An analysis of forensic practice to identify insolvency (bankruptcy) has shown that countries based on the Romano-Germanic legal system, 3 including the Baltic countries, use a normative approach comparing the calculated financial ratios with its normative value (Liodorova et al 2019). The legislative acts establish 10 obligatory ratios that are used in forensic examination to detect bankruptcy fraud in the Russian Federation, the Republic of Belarus and Ukraine.…”
Section: Tablementioning
confidence: 99%